Changes in microbial communities during the spoilage of palm wine stored at room temperature - Constant K. Attchelouwa; Marius D. Akissi; Claude G.Z. Kouadjo; Clémentine A. Kouakou-Kouamé; Corinne Teyssier; Florent K. N’guessan (Brazilian Journal of Microbiology, 2025)

Analytical modeling and correction of the ocean colour bidirectional reflectance across water types - Jaime Pitarch; Vittorio Ernesto Brando; Marco Talone; Constant Mazeran; Davide D'Alimonte; Tamito Kajiyama; Ewa Kwiatkowska; David Dessailly; Juan Ignacio Gossn (Remote Sensing of Environment, 2025)

Comparison of correction methods for bidirectional effects in ocean colour remote sensing - Davide D'Alimonte; Tamito Kajiyama; Jaime Pitarch; Vittorio Ernesto Brando; Marco Talone; Constant Mazeran; Michael Twardowski; Srinivas Kolluru; Alberto Tonizzo; Ewa Kwiatkowska; David Dessailly; Juan Ignacio Gossn (Remote Sensing of Environment, 2025)

Monitoring macroplastics in aquatic and terrestrial ecosystems: Expert survey reveals visual and drone-based census as most effective techniques - L. Gallitelli; P. Girard; U. Andriolo; M. Liro; G. Suaria; C. Martin; A.L. Lusher; K. Hancke; MCM Blettler; O. Garcia-Garin; I.E. Napper; L. Corbari; et al. (Science of The Total Environment, 2024)

Vegetation attributes in peri-urban agroforestry systems and their socio-economic determinants in Benin (West Africa) - Sèdoami Flora Dogbo; Kolawolé Valère Salako; Sylvanus Mensah; D. M. Amandine Akakpo; Achille Ephrem Assogbadjo; Jens Gebauer; Romain Glèlè Kakaï; Constant Yves Adou Yao (Agroforestry Systems, 2024)

The effect of pellet shape on turbulent hydrodynamics in narrow packed beds: A magnetic resonance velocity imaging study - Scott V. Elgersma; Andrew J. Sederman; Michael D. Mantle; Constant M. Guédon; Gary J. Wells; Lynn F. Gladden (Chemical Engineering Journal, 2024)

Magnetic resonance velocity imaging of turbulent gas flow in a packed bed of catalyst support pellets - Scott V. Elgersma; Andrew J. Sederman; Michael D. Mantle; Constant M. Guédon; Gary J. Wells; Lynn F. Gladden (Chemical Engineering Journal, 2023)

Heavy rains control the floating macroplastic inputs into the sea from coastal Mediterranean rivers: A case study on the Têt River (NW Mediterranean Sea) - M. Laverre; P. Kerhervé; M. Constant; L. Weiss; B. Charrière; M. Stetzler; D. González-Fernández; W. Ludwig (Science of The Total Environment, 2023)

Calcifediol is a safe and effective metabolite for raising vitamin D status and improving growth and feed conversion in rainbow trout - S. Rider; V. Verlhac-Trichet; D. Constant; E. Chenal; S. Etheve; B. Riond; H. Schmidt-Posthaus; R. Schoop (Aquaculture, 2023)

Plastic and genetic responses of a common sedge to warming have contrasting effects on carbon cycle processes - Tom W. N. Walker; Wolfram Weckwerth; Luca Bragazza; Lena Fragner; Brian G. Forde; Nicholas J. Ostle; Constant Signarbieux; Xiaoliang Sun; Susan E. Ward; Richard D. Bardgett (Ecology Letters, 2019)
Climate warming affects plant physiology through genetic adaptation and phenotypic plasticity, but little is known about how these mechanisms influence ecosystem processes. We used three elevation gradients and a reciprocal transplant experiment to show that temperature causes genetic change in the sedge Eriophorum vaginatum . We demonstrate that plants originating from warmer climate produce fewer secondary compounds, grow faster and accelerate carbon dioxide ( CO 2 ) release to the atmosphere. However, warmer climate also caused plasticity in E. vaginatum , inhibiting nitrogen metabolism, photosynthesis and growth and slowing CO 2 release into the atmosphere. Genetic differentiation and plasticity in E. vaginatum thus had opposing effects on CO 2 fluxes, suggesting that warming over many generations may buffer, or reverse, the short‐term influence of this species over carbon cycle processes. Our findings demonstrate the capacity for plant evolution to impact ecosystem processes, and reveal a further mechanism through which plants will shape ecosystem responses to climate change.

Molecular identification of yeast, lactic and acetic acid bacteria species during spoilage of tchapalo, a traditional sorghum beer from Côte d’Ivoire - Constant K. Attchelouwa; Florent K. N’guessan; Francine M. D. Aké; Marcellin K. Djè (World Journal of Microbiology and Biotechnology, 2018)

Targeting the Red Nucleus for Cerebellar Tremor - M. Lefranc; M. Manto; P. Merle; M. Tir; D. Montpellier; J.-M. Constant; D. Le Gars; J.-M. Macron; P. Krystkowiak (The Cerebellum, 2014)

Unconjugated Bilirubin Restricts Oligodendrocyte Differentiation and Axonal Myelination - Andreia Barateiro; Veronique E. Miron; Sofia D. Santos; João B. Relvas; Adelaide Fernandes; Charles ffrench-Constant; Dora Brites (Molecular Neurobiology, 2013)

Bioavailability of Reversibly Sorbed and Desorption-Resistant 1,3-Dichlorobenzene from a Louisiana Superfund Site Soil - Sangjin Lee; R. R. Kommalapati; K. T. Valsaraj; J. H. Pardue; W. D. Constant (Water, Air, & Soil Pollution, 2004)

Rate-Limited Desorption of Volatile Organic Compounds from Soils and Implications for the Remediation of a Louisiana Superfund Site - Sangjin Lee; R. R. Kommalapati; K. T. Valsaraj; J. H. Pardue; W. D. Constant (Environmental Monitoring and Assessment, 2002)

Soil-Water Partitioning and Desorption Hysteresis of Volatile Organic Compounds from a Louisiana Superfund Site Soil - R. R. Kommalapati; K. T. Valsaraj; W. D. Constant (Environmental Monitoring and Assessment, 2002)

Copper‐induced release of complexing ligands similar to thiols by Emiliania huxleyi inseawater cultures - M. Fernanda C. Leal; M. Teresa S. D. Vasconcelos; Constant M. G. van den Berg (Limnology and Oceanography, 1999)
Marine microalgae ( Emiliania huxleyi ) were grown in seawater enriched only with nitrogen and phosphorus, without control of free metal concentrations using synthetic chelators. Complexing ligands and thiol compounds were determined by cathodic stripping volt–ammetry. Copper was added to these cultures, and ligands were produced in response to the copper addition. Parallel measurements of thiols showed that glutathione and other unidentified thiols (electrochemically similar to thioacetamide) were produced by the algae at rates and concentrations similar to those of the complexing ligands. Smaller amounts of thiols were produced when ligands including thiols were added to the culture. The results indicate that thiols can account for a major part or most of the copper–complexing ligands produced by these algae. Furthermore, a feedback mechanism exists in which the production of thiol–type complexing ligands is controlled by the free copper concentration, production already being stimulated by an increase of [Cu 2+ ] from 0.4 to 1.5 pM. Incubations with added exudates, thiols, and salicylaldoxime (SA) showed much reduced copper toxicity even though copper uptake was increased by the exudates and the SA.

Partition Constants and Adsorption/Desorption Hysteresis for Volatile Organic Compounds on Soil from a Louisiana Superfund Site - Kalliat T. Valsaraj; Raghava R. Kommalapati; Edward D. Robertson; W. D. Constant (Environmental Monitoring and Assessment, 1999)